Pengembangan Program Pasar UMKM Jago Silo (Jajani Tonggo Nglarisi Bolo) Sebagai Upaya Pemberdayaan Ekonomi Lokal Di Kelurahan Bendogerit Kota Blitar - Ulva Roifatul Lailin; Wydha Mustika Maharani; Wildan Ibnu Batutoh (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This service partner is a business actor who is domiciled in Bendogerit Village, Blitar City and is classified as an economically productive partner. The aim of this service is to create the Jago Silo MSME market (Jajani Tonggo Nglarisi Bolo) as a way to encourage the local economy in Bendogerit Village, Blitar City. It is estimated that the Jago Silo MSME market can become a center of sustainable economic activity that provides benefits for MSME players and society as a whole by involving various parties, including local entrepreneurs, regional government and the community. As a result of Jago Silo activities, local business actors feel that they have received greater financial benefits, which for their partners has contributed to improving their quality of life.